Vállalkozói ökoszisztéma vizsgálata Debrecenben a nyitott innovációs terek szemszögéből - Oláh, Judit; Horváth, Adrienn (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
Innovation is not just a technology, but it is rather a comprehensive vision of what the future should look like and which requires changes in many ambits. Innovation is driven by people's needs, ambitions and dreams, and it is necessary that people at different positions in the society change the way they work and live. Innovation, as a result of human interactions, often fails because people do not understand each other, as they belong to different worlds which have their own languages and cultures. While innovation system-like thinking recognizes that the needs are a good mix of factors for innovation, it is hard to establish the perfect mix beforehand: innovation systems and policies need to be adaptive. We tried to bring this complex vision to our future. The actuality of the topic is provided by the fact that we are in the period of the development of digital industrial revolution, on the peak of the technology innovations, slowly resulting in the revolutions of the machines.